Distribution, Characterization and Dynamics of Soil enzymes in Selected Soils of Kerala - Aparna B (Department Of Soil Science And Agricultural Chemistry,College Of Agriculture, 2000)
Biologically and biochemically mediated processes in soils are ••• fundamental to the functioning of terrestial ecosystem. Understanding the ,A underlying biological processes in tandem with identification of indicators of ecosystem stress is inevitable to provide strategies and approaches to promote long term sustainability of the fragile ecosystem. All members of the food chain are dependent on the soil as a source of nutrients, support and sustenance besides their reliance on soil as a sink for terrestial wastes. Now there is growing evidence to believe that soil biological parameters can hold potential as early and sensitive indices of soil degradation or restoration. In this context, soil enzymes play an active role in the microbial ecology and transformations brought about by catalysing enumerable reactions in soils. The activity of soil enzymes thus hold potential as soil quality indicators though they are sensitive to temporal changes due to environmental and management factors. Thus the long term effects of soil management techniques such as crop rotation, liming, fertilization and pesticide applications on the biological regimes need detailed investigations. Hence, with the overriding objective of projecting the effects of long term fertilization, application of soil amendments and agrochemicals on enzyme activities in relation to soil fertility, the present investigation was carried out.